ANALISIS PEMBIAYAAN PENDIDIKAN DI DAERAH TERTINGGAL - Bambang Sriyanto; Amin Imroni Rosyid; Sutrisno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Inequalities in education funding in Indonesia’s underdeveloped regions remain a serious problem that affects the quality of education received. This study aims to analyze the education financing system in underdeveloped regions and identify the challenges faced. The method used is a systematic literature review (SLR) employing the PRISMA approach through the selection and screening of articles based on specific criteria. The literature search yielded eight articles, which were analyzed thematically. The results indicate that financing in 3T regions is still dominated by BOS funds, which are not yet optimally utilized as they are primarily focused on basic needs, and are further constrained by high operational costs, limited resources, and low community participation. Therefore, more adaptive financing policies grounded in local needs, along with more effective fund management, are required to support equitable distribution and improvements in educational quality.